Characterization of phenyl pyrimidine derivatives that inhibit cytomegalovirus immediate-early gene expression. Issue 1 (March 2018) - Yamada, Koh-Hei; Majima, Ryuichi; Yamaguchi, Toyofumi; Inoue, Naoki
Background: Previously, we established a reporter cell line for human cytomegalovirus and screened anti-human cytomegalovirus compounds using the cell line. In this study, we characterized one of the identified compounds, 2, 4-diamino-6–(4-methoxyphenyl)pyrimidine (coded as 35C10). Methods: 50% Effective concentrations (EC50s) and 50% cytotoxic concentrations (CC50s) of 35C10 and its derivatives in human fibroblasts were determined by X-gal staining of the cells infected with human cytomegalovirus Towne strain expressing β-galactosidase. Results: EC50 and CC50 of 35C10 were 4.3 µM and >200 µM, respectively. Among several 35C10 derivatives, only one lacking 4-amino group of pyrimidine showed a similar EC50. 35C10 weakly inhibited murine cytomegalovirus, herpes simplex virus type 1, and varicella-zoster virus. A "time of addition" experiment suggested that 35C10 inhibited an early phase of the infection. Although 35C10 did not inhibit viral attachment to the cells nor the delivery of viral DNA to the nuclei, it decreased the number of infected cells expressing immediate-early 1 and 2 (IE1/IE2) proteins. 35C10 also inhibited the activation of a promoter for TRL4 in the reporter cells upon human cytomegalovirus infection, but not in the same reporter cells transfected with a plasmid expressing IE2. Conclusion: Our findings suggest that 35C10 is a novel compound that inhibits IE gene expression in human cytomegalovirus-infected cells.